2022
DOI: 10.3844/ajavsp.2022.288.293
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestibility of Hay Mangrove with Native Grass

Abstract: Forage is the main component of feed given to ruminants. Local feed ingredients that can be used are mangroves and native grass. This study used the Randomized Block Design (RBD) experimental method with 4 = four treatments and 5-five replications. The treatments composed of Hay Mangrove Leaves and Native grass as follows: A (60 + 40%), B (50 + 50%), C (40 + 60%) and D (30 + 70%). Data were analyzed using General Liner Model and continued with Duncan's Multiple Range Tests (DMRT). The results showed that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Providing mangrove leaves, combined with fermented M. diversifolia, in complete rations is expected to meet the nutritional needs of ruminants and increase body weight, especially in Kacang goats. Sari et al (2022b;2022c) reported that a combination of 16% mangrove leaf hay with 24% field grass, 10% rice straw, and 50% concentrate for Kacang goats gave the best digestibility results of crude fiber, crude fat, and NFE, which were 67.98, 63.73, and 61.38%, respectively. However, the practice of using a combination of mangrove leaf hay and fermented M. diversifolia as goat feed has not been widely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Providing mangrove leaves, combined with fermented M. diversifolia, in complete rations is expected to meet the nutritional needs of ruminants and increase body weight, especially in Kacang goats. Sari et al (2022b;2022c) reported that a combination of 16% mangrove leaf hay with 24% field grass, 10% rice straw, and 50% concentrate for Kacang goats gave the best digestibility results of crude fiber, crude fat, and NFE, which were 67.98, 63.73, and 61.38%, respectively. However, the practice of using a combination of mangrove leaf hay and fermented M. diversifolia as goat feed has not been widely adopted.…”
Section: Introductionmentioning
confidence: 99%